Evaluation of parameters in the bio-oxidation process of refractory gold minerals - Aguirre Chamba, P. (2017)
The mining districts located in the western mountain range in the south of Ecuador have gold minerals with refractory characteristics, which do not allow gold recovery by traditional methods used in Ecuador. Therefore, it is necessary to apply some technology that permits to obtain greater metal recovery. Bio-oxidation, as treatment of refractory ores that contain low grade of gold, offers an economic and sustainable alternative for this purpose. The objective of this research was to evaluate the effect of particle size, pulp density and concentration of inoculum and inducer (Fe+2) on the bio-oxidation of refractory gold minerals in order to maximize gold recovery of the bioleached minerals by means of a cyanidation process. The microbial consortium used in this work was collected and isolated from the Portovelo mining district corresponding mostly to Acidithiobacillus ferrooxidans and Leptospirillum ferrooxidans species. The Eh, final concentration of ferric ion, total iron and sulfates were measured. Finally, the bio-oxidized material was tested using cyanidation to determine the gold recovery. The results after the cyanidation tests showed that the highest gold recovery was obtained when the bio-oxidation step was conducted with 68-91 ?m particle size, 15% pulp density, 20% v/v inoculum and 2 g/L of Fe2+ as inducer. At those conditions, gold recovery was 68% compared to 26% obtained when no bio-oxidation step was performed, demonstrating that this process was favorable compared with traditional gold recovery processes.